2009
DOI: 10.1038/onc.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pools of cancer stem-like cells coexist within human glioblastomas and display different tumorigenicity and independent genomic evolution

Abstract: Glioblastomas (GBMs) contain transformed, self-maintaining, multipotent, tumour-initiating cancer stem cells, whose identification has radically changed our perspective on the physiology of these tumours. Currently, it is unknown whether multiple types of transformed precursors, which display alternative sets of the complement of properties of true cancer stem cells, can be found in a GBM. If different subsets of such cancer stem-like cells (CSCs) do exist, they might represent distinct cell targets, with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
174
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(187 citation statements)
references
References 14 publications
13
174
0
Order By: Relevance
“…CSCs have been reported in brain tumors, especially in glioblastoma multiforme (GBM) [61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The stemlike GBM cells have been enriched using cell surface molecules, such as CD133 [61,72], SSEA-1 (stagespecific embryonic antigen-1) [64], EGFR [67,68], and CD44 [69], or functional assays, including the SP analysis [7,63,73] and neurosphere assays [49,74].…”
Section: Csc Heterogeneitymentioning
confidence: 99%
“…CSCs have been reported in brain tumors, especially in glioblastoma multiforme (GBM) [61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The stemlike GBM cells have been enriched using cell surface molecules, such as CD133 [61,72], SSEA-1 (stagespecific embryonic antigen-1) [64], EGFR [67,68], and CD44 [69], or functional assays, including the SP analysis [7,63,73] and neurosphere assays [49,74].…”
Section: Csc Heterogeneitymentioning
confidence: 99%
“…4 Photograph of two nuclei (arrows) from a glioma cell (red) and a normal astrocyte (unlabeled). Nanoparticles (green) carrying a tumor-specific antibody bind with the tumor cell and not the astrocyte stem cells that are more resistant to radiotherapy and chemotherapy than the more lineage-defined cells [11,13,14,19,23]. These stem cells may be a source of gliomas and may be one of the reasons these tumors fail to respond more effectively to current treatment.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…5,6 In contrast, the pathologic substrates of DAWM abnormalities have been investigated only recently. 1,4 Moore et al 1 demonstrated a loss of myelin phospholipids as well as axonal reduction whose extents are intermediate between those of discrete lesions and NAWM.…”
mentioning
confidence: 99%
“…Inhibitors of this secretase are being tried in patients with leukemia and are being considered for treatment of children with advanced ependymoma within the US Pediatric Brain Tumor Consortium. [1][2][3][4][5] Conventional therapies tend to kill normal and tumor cells but not the resistant brain tumor stem cells that eventually regenerate the tumor (this is the reason why glioblastomas always recur). In addition, the effect of conventional therapies on tumor cells is limited as they cannot effectively target all of the different cell lineages.…”
mentioning
confidence: 99%
See 1 more Smart Citation